Realization of a cascade treatment algorithm for glaucoma in St. Petersburg - A.V. Antonova; V.P. Nikolaenko; V.V. Brzheskiy (РМЖ "Клиническая офтальмология")
A.V. Antonova1, V.P. Nikolaenko1,2, V.V. Brzheskiy3 1City Multidisciplinary Hospital No. 2, St. Petersburg, Russian Federation 2St. Petersburg State University, St. Petersburg, Russian Federation 3St. Petersburg State Pediatric Medical University, St. Petersburg, Russian Federation Aim: to analyze the duration and regimen of topical treatment and the pattern of prior laser and surgical procedures in patients with glaucoma who were admitted to the hospital for IOP-lowering interventions. Patients and Methods: this study included 500 consecutively enrolled patients who underwent surgery for uncontrolled glaucoma in 2016–2020 and were followed up for 6–24 months. Disease history, cumulative "preservative" load, clinical examinations, and surgical outcomes were assessed. Results: preoperatively, most patients received the maximum medical therapy (i.e., three agents in two bottles). Simultaneous use of all four major classes of IOP-lowering medications occurred in 10% of patients only. Two-third of patients required surgical interventions to reduce IOP after a 6-year medical therapy. By the time of admission, 60% of patients were diagnosed with advanced or end-stage glaucoma. Prior laser or surgical procedures to reduce IOP were performed only in 142 patients and 52 patients, respectively. Treatment adherence was lower in men compared to women, irrespective of its stage. Conclusion: most patients received adequate medical therapy. However, in general, surgery was performed too late. It gives the impression that the efficacy of therapeutic and laser stages of cascade glaucoma treatment is no more than five years. In addition to the obvious drawbacks of a laissez-faire strategy (irreversible vision loss), the risk of surgical failure significantly increases. Long-term (at least 3-year) therapy using (non)fixed-dose combinations of agents containing preservatives is the major modifiable risk factor for early filtration loss. Preservative-free prostaglandin analogues improve treatment tolerability, adherence to treatment, and chances for success of IOP-lowering surgery. The authors’ results demonstrate that gender differences should be considered when planning treatment and follow-up visits. Keywords: glaucoma, IOP-lowering therapy, glaucoma surgery, ocular surface, preservatives, benzalkonium chloride. For citation: Antonova A.V., Nikolaenko V.P., Brzheskiy V.V. Realization of a cascade treatment algorithm for glaucoma in St. Petersburg. Russian Journal of Clinical Ophthalmology. 2021;21(3):123–128 (in Russ.). DOI: 10.32364/2311-7729-2021-21-3-123-128.